Combined chain- and step-growth dispersion polymerization toward PSt particles with soft, clickable patches. Issue 8 (27th January 2017) - Jiang, Kun; Liu, Yanan; Yan, Yaping; Wang, Shengliu; Liu, Lianying; Yang, Wantai
Abstract : Particles with a hard body and soft, clickable dimple- or bulge-patches are prepared by simple combined chain- and step-growth dispersion polymerization. Abstract : Simple and convenient synthetic methods are highly in demand for the preparation and application of patchy particles (PPs) with diverse morphologies, functionalities and behaviors. Very recently, step-growth heterogeneous click polymerizations have been developed to fabricate monodisperse, spherical, soft and clickable particles. However, so far, this technique has seldom involved forming structures (core–shell, or pores, etc. ), anisotropic shapes and compositions of particles. Herein, we prepare PPs with a hard body and soft, clickable dimple- or bulge-patches by incorporating step-growth thiol–ene polymerizations into the chain-growth polymerization of styrene (St) in a dispersion system. The phase separation between thiol–ene polymers and PSt in growing particles occurs due to their differences in the glass transition temperature ( T g ) and hydrophilicity, forming core–shell and dimple- or bulge-patched particles. SEM and TEM images of the degraded particles confirm that the patches are primarily composed of click polymers. Varying the addition time, amounts, feed ratio and type of thiol/ene monomer, degree of phase separation, shape, number and size of patches, and contents of thiol/ene segments in/on patches are tuned flexibly. FI-IR analyses reveal that off-stoichiometric thiol and ene segments are incorporated, owing to off-stoichiometric thiol–ene reactions concurrent with the polymerization of St, even when stoichiometric thiol and ene are added. Moreover, Fe3 O4 or Ag nanoparticles are attached on the PSt body with –SO 3− groups or on click polymer patches with –SH groups. Post-modifications of PPs are carried out through reactions of excess –SH or –CC– groups on patches with –CC– or –SH group-containing monomers. Superhydrophobic or hydrophilic particulate films, or fluorescent tagged PPs are prepared.